Comparison of Ustekinumab Trough Concentrations Measured by 2 ELISA Kits and Evaluation of Clinical Response in Crohn's Disease. Issue 4 (18th August 2022) - Kwon, Yiyoung; Kang, Ben; Kim, Eun Sil; Choe, Yon Ho; Kim, Mi Jin
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Ustekinumab is a recently introduced biological agent for the treatment of Crohn's disease. The clinical use of the trough concentration of ustekinumab is not as standardized as that of infliximab. The authors aimed to introduce a measurement method and the results of trough concentrations of ustekinumab in clinical applications. Methods: Thirty-two blood samples from 10 young adult patients diagnosed with Crohn's disease were analyzed. During the maintenance treatment, injection intervals were shortened from 12 weeks to 8 weeks in 4 patients who exhibited a loss of response. Ustekinumab trough concentrations were measured using 2 commercial ELISA kits, kit A and kit B. Results: The median trough concentrations measured with kits A and B were 0.26 and 0.38 mcg/mL, respectively. In the case of kit A, low trough concentrations were undetected on many occasions and measured as zero, whereas kit B displayed their relative values even at low concentrations. Poor clinical parameters, elevated erythrocyte sedimentation rate, C-reactive protein, and calprotectin levels were significantly correlated with lower trough concentrations ( P < 0.05). The area under the receiver operating characteristics curve of kit B (0.921) was greater than that of kit A (0.744). The optimal cutoff values for prediction clinical responses were 0.17 and 0.41 mcg/mL for kit A and kit B, respectively. Conclusions: The trough concentration of ustekinumab measured by the 2 ELISA kits correlated with laboratory results that indicated the activity of Crohn's disease. Furthermore, kit B detected even minute changes in trough concentrations.